Characterization of Blood Mucosal‐Associated Invariant T Cells in Patients With Axial Spondyloarthritis and of Resident Mucosal‐Associated Invariant T Cells From the Axial Entheses of Non‐Axial Spondyloarthritis Control Patients. Issue 11 (22nd September 2022) - Rosine, Nicolas; Rowe, Hannah; Koturan, Surya; Yahia‐Cherbal, Hanane; Leloup, Claire; Watad, Abdulla; Berenbaum, Francis; Sellam, Jeremie; Dougados, Maxime; Aimanianda, Vishukumar; Cuthbert, Richard; Bridgewood, Charlie; et al.
Abstract : Objective: The importance of interleukin‐17A (IL‐17A) in the pathogenesis of axial spondyloarthritis (SpA) has been demonstrated by the success of IL‐17A blockade. However, the nature of the cell populations that produce this important proinflammatory cytokine remains poorly defined. We undertook this study to characterize the major IL‐17A–producing blood cell populations in the peripheral blood of patients with axial SpA, with a focus on mucosal‐associated invariant T (MAIT) cells, a population known to be capable of producing IL‐17. Methods: We evaluated IL‐17A production from 5 sorted peripheral blood cell populations, namely, MAIT cells, γδ T cells, CD4+ T cells, CD8+ T cells, and neutrophils, before and after stimulation with phorbol myristate acetate, the calcium ionophore A23187, and β‐1, 3‐glucan. Expression of IL‐17A transcripts and protein were determined using nCounter and ultra‐sensitive Simoa technology, respectively. MAIT cells from the axial entheses of non‐axial SpA control patients (n = 5) were further characterized using flow cytometric immunophenotyping and quantitative polymerase chain reaction, and the production of IL‐17 was assessed following stimulation. Results: On a per‐cell basis, MAIT cells from peripheral blood produced the most IL‐17A compared to CD4+ T cells ( P  < 0.01), CD8+ T cells ( P  < 0.0001), and γδ T cells ( P  < 0.0001). IL‐17A was not produced by neutrophils. Gene expression analysis also revealed significantly higher expression of IL17A and IL23R in MAIT cells. Stimulation of peripheral blood MAIT cells with anti‐CD3/CD28 and IL‐7 and/or IL‐18 induced strong expression of IL17F . MAIT cells were present in the normal, unaffected entheses of control patients who did not have axial SpA and showed elevated AHR, JAK1, STAT4, and TGFB1 transcript expression with inducible IL‐17A protein. IL‐18 protein expression was evident in spinal enthesis digests. Conclusion: Both peripheral blood MAIT cells and resident MAIT cells in normal axial entheses contribute to the production of IL‐17 and may play important roles in the pathogenesis of axial SpA.